Executive functioning in older adults with hoarding disorder. (26th February 2013) - Ayers, Catherine R.; Wetherell, Julie Loebach; Schiehser, Dawn; Almklov, Erin; Golshan, Shahrokh; Saxena, Sanjaya
<x xml:space="preserve">Abstract</x> Background Hoarding disorder (HD) is a chronic and debilitating psychiatric condition. Midlife HD patients have been found to have neurocognitive impairment, particularly in areas of executive functioning, but the extent to which this is due to comorbid psychiatric disorders has not been clear. Aims/Method The purpose of the present investigation was to examine executive functioning in geriatric HD patients without any comorbid Axis I disorders (n = 42) compared with a healthy older adult comparison group (n = 25). We hypothesized that older adults with HD would perform significantly worse on measures of executive functioning (Wisconsin Card Sort Task [Psychological Assessment Resources, Lutz, Florida, USA] ( Psychological Assessment Resources, 2003) and the Wechsler Adult Intelligence Scale‐IV digit span and letter–number sequencing tests [Pearson, San Antonio, TX, USA]). Results Older adults with HD showed significant differences from healthy older controls in multiple aspects of executive functioning. Compared with healthy controls, older adults with HD committed significantly more total, non‐perseverative errors and conceptual level responses on the Wisconsin Card Sort Task and had significantly worse performance on the Wechsler Adult Intelligence Scale‐IV digit span and letter–number sequencing tests. Hoarding symptom severity was strongly correlated with executive dysfunction in the HD group. Conclusions Compared with demographically‐matched controls, older adults with HD have dysfunction in several domains of executive functioning including mental control, working memory, inhibition, and set shifting. Executive dysfunction is strongly correlated with hoarding severity and is not because of comorbid psychiatric disorders in HD patients. These results have broad clinical implications suggesting that executive functioning should be assessed and taken into consideration when developing intervention strategies for older adults with HD. Copyright © 2013 John Wiley & Sons, Ltd.